Strategi Komunikasi Digital Berbasis Bahasa Ngapak dalam Membangun Keterlibatan Audiens pada Konten TikTok - Yulia Faramudita; Didi Permadi; Ike Desi Florina (Universitas Medan Area, 2026)
The rapid development of digital media has encouraged content creators to utilize regional languages as communication strategies to strengthen audience engagement while reinforcing cultural identity. Although previous studies have examined the use of local languages on social media, research specifically explaining how the Ngapak language functions as a digital communication strategy for building audience engagement through the perspective of symbolic interactionism remains limited. This study aims to analyze the Ngapak language-based digital communication strategy employed by the TikTok accounts @RofiqKompak and @Mamichula in fostering audience engagement. A qualitative approach was employed using Herbert Blumer's Symbolic Interactionism framework, emphasizing the concepts of meaning, language, and thought. Data were collected through content observation, documentation, and analysis of audience interactions in the comment sections. The findings reveal that the Ngapak language functions not only as a communication tool but also as a symbol of cultural identity that creates meaning, emotional closeness, and social relationships between creators and audiences. The @RofiqKompak account utilizes Ngapak as a personal branding strategy by combining local identity with experiences of working in South Korea, whereas @Mamichula employs Ngapak to reinforce communication authenticity despite visual characteristics that initially lead audiences to perceive the creator as a foreigner. The findings further demonstrate that the use of the Ngapak language encourages audience participation through comments, likes, and shares while strengthening creator identity and fostering digital community formation on TikTok. This study contributes to the development of digital communication literature by highlighting the strategic role of local cultural identity within symbolic interactionism and offers practical implications for content creators in designing authentic, contextual, and engagement-oriented digital communication strategies.